2014
DOI: 10.1186/1472-6920-14-76
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the effectiveness of multisource feedback in improving the professional practice of medical doctors: a systematic review

Abstract: BackgroundMultisource feedback (MSF) is currently being introduced in the UK as part of a cycle of performance review for doctors. However, although it is suggested that the provision of feedback can lead to a positive change in performance and learning for medical professionals, the evidence supporting these assumptions is unclear. The aim of this review, therefore, was to identify the key factors that influence the effectiveness of multisource feedback in improving the professional practice of medical doctor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
116
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(129 citation statements)
references
References 44 publications
2
116
0
6
Order By: Relevance
“…22 The impact of physician feedback has been correlated with the knowledge and credibility of the person who provides the feedback. 23 We observed a further reduction of cranial CT rates temporally related to providers receiving annual CT reports delivered by the ED division chief. The primary impact was to reduce variability in CT rates between ED providers.…”
Section: Discussionmentioning
confidence: 68%
“…22 The impact of physician feedback has been correlated with the knowledge and credibility of the person who provides the feedback. 23 We observed a further reduction of cranial CT rates temporally related to providers receiving annual CT reports delivered by the ED division chief. The primary impact was to reduce variability in CT rates between ED providers.…”
Section: Discussionmentioning
confidence: 68%
“…Intention to change cannot be proven to result in actual change (Webb & Sheeran, 2006) and it could be argued that healthcare systems are more concerned with behaviour change resulting in better patient care than intention to improve or self-reported improvements. However measuring impact on patient care in this area is difficult and health psychology theories such as theory of planned behaviour (Ajzen & Madden, 1986) and protection motivation theory (Rogers, 1985) assume intentions cause behaviour (Ferguson, Wakeling & Bowie, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For example, facilitation of feedback in order to promote effective reflection (Overeem et al, 2009b).The reflection literature proposes that reflection is a key step in integrating new information and learning (Moon, 2004). It also appears important to consider MSF tools carefully in order to gain maximum benefit; including having enough participants (Lelliott et al, 2008), multiple perspectives (Ferguson, Wakeling & Bowie, 2014;Overeem et al, 2010), patients Sargeant, Mann & Ferrier, 2005;Sargeant et al, 2007) and free text (Ferguson, Wakeling & Bowie, 2014;Overeem et al, 2010). It would also be pertinent to educate those asked to complete MSF feedback (Canavan et al, 2010;Saedon, Saedon & Aggarwal, 2010), as feedback is generally shown to be a positive force for learning over time , but needs to be specific, constructive and useful (Ferguson, Wakeling & Bowie, 2014;Overeem et al, 2009b;Sargeant, Mann & Ferrier, 2005;Sargeant et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations